2019
DOI: 10.1016/j.cels.2019.01.003
|View full text |Cite
|
Sign up to set email alerts
|

Quantifying Drug Combination Synergy along Potency and Efficacy Axes

Abstract: Highlights d MuSyC is a synergy framework applicable to any metric of drug combination effect d Unlike other methods, MuSyC decouples synergy of potency and efficacy d It subsumes traditional synergy methods, resolving ambiguities and biases in the field d MuSyC reveals optimal co-targeting strategies in NCSLC and melanoma

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
198
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 166 publications
(207 citation statements)
references
References 50 publications
(87 reference statements)
0
198
0
Order By: Relevance
“…A recently developed multi-dimensional framework (MuSyC) uses a two-dimensional extension of Hill equation to distinguish synergistic efficacy versus synergistic potency, thereby allowing for a comprehensive understanding of drug interactions. Such understanding not only helps with improving therapeutic efficacy via enhancing effect, but also reducing off-target toxicities via dose reduction [10]. Probabilistic phenotype rate constants follow dose-response patterns suitable to be fit by Hill equation and therefore could be used as input to platforms such as MuSyC.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A recently developed multi-dimensional framework (MuSyC) uses a two-dimensional extension of Hill equation to distinguish synergistic efficacy versus synergistic potency, thereby allowing for a comprehensive understanding of drug interactions. Such understanding not only helps with improving therapeutic efficacy via enhancing effect, but also reducing off-target toxicities via dose reduction [10]. Probabilistic phenotype rate constants follow dose-response patterns suitable to be fit by Hill equation and therefore could be used as input to platforms such as MuSyC.…”
Section: Discussionmentioning
confidence: 99%
“…In the case of cancer drugs, synergistic interactions are typically assessed on the basis of bulk cell population measurements, such as relative viability (normalized cell count) and net growth rate inhibition, and their variations with drug dose and combination [5][6][7][8][9]. The benefit of drug combination is then evaluated based on whether using two drugs together improves the potency (via minimizing the dose) or efficacy of treatment (via enhancing the effect) as compared with using either of the drugs alone [10][11][12][13][14][15][16]. The benefit of drug combination with respect to efficacy and potency, however, may be decoupled [10], as each metric encodes distinct information about cellular response to a drug [17].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…RNASeq of melanoma cell lines (SKMEL5 subclones) was performed as previously reported (Meyer et al, 2019) . Transcript count data from Gene Expression Omnibus (Accession number: GSE122041, https://www.ncbi.nlm.nih.gov/geo/query/acc.cgi?acc=GSE122041 ) was used for downstream analysis performed in R ( https://www.r-project.org ).…”
Section: Methods Details Cell Culture and Chemical Reagentsmentioning
confidence: 99%
“…We recently reported that BRAF -mutated melanoma cell lines, including isogenic single-cell derived subclones, exhibit varying drug sensitivities to a small molecule BRAF kinase inhibitor (BRAFi) (Hardeman et al, 2017;Paudel et al, 2018) . Using Drug-Induced Proliferation (DIP) rates ( Table S1 ) (Harris et al, 2016) , as a measure of drug effects, we examined the molecular correlates of BRAF i sensitivity, and reported that top 200 differentially expressed genes (DEGs) in drug-insensitive cells were enriched in processes and functions related to redox metabolism (Meyer et al, 2019) . Here, we extended our analysis to examine all significant DEGs among isogenic subclones ( Table S2 ) using their RNASeq profiles.…”
Section: Gene Expressions and Flux Balance Analyses Reveal Enhanced Cmentioning
confidence: 99%